FinTech Innovations : Transforming the Landscape of Personal Finance Management - Siti Nurkholisah; Mochamad Syafii; Rusdiyanto Rusdiyanto (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the evolving landscape of personal finance management (PFM) in the digital era, focusing on the transformative role of financial technology (FinTech). The research addresses the problem of insufficient understanding regarding the interplay between FinTech features and user behavior in achieving financial effectiveness. The primary objective is to conceptualize how FinTech innovation, user interface (UI) quality, user trust, and digital literacy collectively influence PFM outcomes. A qualitative literature review method was employed, analyzing over 20 peer reviewed articles published between 2020 and 2025. The findings reveal that FinTech innovation and UI quality directly enhance financial decision making by improving automation and user experience. However, their impact is significantly mediated by user trust and moderated by digital literacy. These psychological and cognitive factors determine whether technological features lead to sustained engagement and improved financial behavior. The synthesized model illustrates a multidimensional framework where technological sophistication must be complemented by trust and digital competence to achieve meaningful financial outcomes. The study concludes that FinTech’s potential in enhancing PFM lies not only in its features but in its ability to foster user confidence and capability. This integrative approach provides valuable insights for FinTech developers, policymakers, and educators aiming to promote inclusive and effective digital finance solutions.